ON CLOSED BCH-ALGEBRA WITH RESPECT TO AN ELEMENT OF A BCH-ALGEBRA - Hussein Hadi Abbass (Journal of Kufa for Mathematics and Computer, 2011)
In this paper, we define the concepts of a closed ideal with respect to an element of a BCH-algebra and a closed BCH-algebra with respect to an element of BCH-algebra . We stated and proved some theorems which determine the relationship between these notion and the notions of some ideals of a BCH-algebra.